Pregnancy in women with dilated cardiomyopathy genetic variants - Restrepo-Córdoba, María Alejandra; Chmielewski, Przemyslaw; Truszkowska, Grażyna; Peña-Peña, María Luisa; Kubánek, Miloš; Krebsová, Alice; Lopes, Luis R; García-Ropero, Álvaro; Merlo, Marco; Paldino, Alessia; Peters, Stacey; Jurcut, Ruxandra; et al. (Revista espanola de cardiologia (English ed.), 2025)
INTRODUCTION AND OBJECTIVES: Limited information is available on the safety of pregnancy in patients with genetic dilated cardiomyopathy (DCM) and in carriers of DCM-causing genetic variants without the DCM phenotype. We assessed cardiac, obstetric, and fetal or neonatal outcomes in this group of patients. METHODS: We studied 48 women carrying pathogenic or likely pathogenic DCM-associated variants (30 with DCM and 18 without DCM) who had 83 pregnancies. Adverse cardiac events were defined as heart failure (HF), sustained ventricular tachycardia, ventricular assist device implantation, heart transplant, and/or maternal cardiac death during pregnancy, or labor and delivery, and up to the sixth postpartum month. RESULTS: A total of 15 patients, all with DCM (31% of the total cohort and 50% of women with DCM) experienced adverse cardiac events. Obstetric and fetal or neonatal complications were observed in 14% of pregnancies (10 in DCM patients and 2 in genetic carriers). We analyzed the 30 women who had been evaluated before their first pregnancy (12 with overt DCM and 18 without the phenotype). Five of the 12 (42%) women with DCM had adverse cardiac events despite showing NYHA class I or II before pregnancy. Most of these women had a history of cardiac events before pregnancy (80%). Among the 18 women without phenotype, 3 (17%) developed DCM toward the end of pregnancy. CONCLUSIONS: Cardiac complications during pregnancy and postpartum were common in patients with genetic DCM and were primarily related to HF. Despite apparently good tolerance of pregnancy in unaffected genetic carriers, pregnancy may act as a trigger for DCM onset in a subset of these women.
Keywords: dospělí; Female; Phenotype; Pregnancy Complications, Cardiovascular; Adult; ženské pohlaví; Variante genética; lidé; Dilated cardiomyopathy; Pregnancy Outcome; těhotenství; Miocardiopatía dilatada; Mutation; Genetic Variation; dilatační kardiomyopatie; Embarazo; výsledek těhotenství; Heart failure; fenotyp; Cardiomyopathy, Dilated; Pregnancy; genetická variace; Insuficiencia cardiaca; kardiovaskulární komplikace v těhotenství; Humans